Understanding problematic eating in out-of-home care: The role of attachment and emotion regulation. (1st April 2019) - Norrish, Anna; Cox, Rachael; Simpson, Angela; Bergmeier, Heidi; Bruce, Lauren; Savaglio, Melissa; Pizzirani, Bengianni; O'Donnell, Renee; Smales, Madelaine; Skouteris, Helen
Abstract: Children living in Out-of-Home Care (OoHC) are thought to be especially vulnerable to developing problematic eating behaviours due to their likelihood of having insecure attachment styles and emotion regulation deficits. Despite this increased risk, our understanding of problematic eating among children in OoHC is limited. Therefore, this study aimed to; (1) Explore the rate of problematic eating behaviours among children living in OoHC, specifically residential and foster care; (2) Investigate how carers manage problematic eating and (3) Understand carers' perceptions of the role of attachment and emotion regulation in relation to problematic eating in OoHC. Semi-structured interviews, focus groups, and surveys were conducted with residential care staff (n = 36) and foster carers (n = 8) in Victoria, Australia. Interviews were recorded, transcribed, and analysed for themes, and frequency data from the survey were generated. Residential and foster carers reported that approximately 38% of the children in their care displayed problematic eating behaviours at a clinical level. Both residential and foster carers commonly understood these behaviours as a function of the child's experiences of food deprivation and limited access to healthy foods prior to entering care which, they believe, has contributed to problems with regulating food intake and/or willingness to try new foods. Carers also commonly reported that the children in their care struggle to form attachments or regulate their emotions, which impacts carers ability to manage problematic eating. It is recommended that future interventions prioritise educating community service organisations (CSOs), responsible for delivering OoHC, to better recognise and address problematic eating behaviours. This will enable CSOs to train their residential and foster carers about how best to respond to and manage problematic eating behaviours.